Applied Deep Learning with Keras : Solve complex real-life problems with the simplicity of Keras /: Solve complex real-life problems with the simplicity of Keras. (2019) - Bhagwat, Ritesh; Abdolahnejad, Mahla; Moocarme, Matthew
No abstract available